Enterococcus plantarum sp. nov., isolated from plants - Svec, Pavel; Vandamme, Peter; Bryndová, Hana; Holochová, Pavla; Kosina, Marcel; Maslanová, Ivana; Sedlácek, Ivo (International journal of systematic and evolutionary microbiology, 2012)
Eight Gram-positive, catalase-negative bacterial strains were isolated during screening of enterococcal populations on plants. rep-PCR fingerprinting using the (GTG)(5) primer showed that the isolates constituted a single cluster that was separate from all known enterococcal species. 16S rRNA gene sequence phylogenetic analysis of three representative strains showed that the isolates belonged to the genus Enterococcus and that they clustered with the Enterococcus faecalis species group. Sequencing of the genes for the phenylalanyl-tRNA synthase alpha subunit (pheS) and the RNA polymerase alpha subunit (rpoA) also revealed the isolates' separate taxonomic position. Application of whole-cell protein fingerprinting, automated ribotyping and extensive phenotyping demonstrated the genetic and phenotypic homogeneity of the isolates and confirmed their separate position within the E. faecalis species group. The isolates represent a novel species of the genus Enterococcus, for which the name Enterococcus plantarum sp. nov. is proposed; the type strain is CCM 7889(T) (=LMG 26214(T)=C27(T)).
Keywords: Molecular Sequence Data; katalasa; Cluster Analysis; Plants; DNA-Directed RNA Polymerases; Catalase; Molecular Typing; DNA řízené RNA-polymerasy; sekvenční analýza DNA; DNA bakterií; RNA, Ribosomal, 16S; rostliny; techniky typizace bakterií; DNA, Ribosomal; shluková analýza; fenylalanin-tRNA-ligasa; molekulární sekvence - údaje; molekulární typizace; fylogeneze; Phenylalanine-tRNA Ligase; Enterococcus; Bacterial Typing Techniques; Sequence Analysis, DNA; Phylogeny; DNA, Bacterial; ribozomální DNA; RNA ribozomální 16S